On survivor stocks in the S&P 500 stock index - Klaus Grobys (Journal of Risk and Financial Management, 2022)
This paper investigates the performance and characteristics of survivor stocks in the S&P 500 index. Using both in-sample and out-of-sample comparisons, survivor stocks outperformed this market index by a considerable margin. Relative to other S&P 500 index companies, survivor stocks tend to be small-value stocks that exhibit high profitability and invest conservatively. Surprisingly, survivor stocks tend to be loser stocks with negative exposure to the momentum factor. Further analyses show that the volatility of the survivor stocks portfolio is less exposed to tail risks and responds less to shocks in the innovation process.
Keywords: G10; G12; G15; G19; 330; asset pricing; S&P 500 index; survivor stocks; risk factors; momentum